Evaluation Of Mycorrhizal And Moringa Leaf Fertilizer On The Chili’s Vegetative - Ambar Susanti (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to test the effect of mycorrhizae and organic moringa leaf fertilizer on the vegetative growth of chili plants. The study was conducted at the agricultural laboratory of KH.A. Wahab Hasbullah University (UNWAHA) in June – October 2025. It was done through an experimental method. The study used a Completely Randomized Design (CRD), using 4 treatments with 5 replications each. The treatments used were Ap0 (control, without additional fertilizer), Ap1 (75% soil + 25% moringa leaf compost), Ap2 (75% soil + 25% mycorrhizal bioagent fertilizer), and Ap3 (75% soil + a combination of 12% moringa leaf compost and 12% mycorrhizal bioagent fertilizer). Data analysis used Duncan's Multiple Range Mean Difference Test (DMRT) with a 5% level. The observation time was 7, 14, 21, and 28 days after planting. The result were The application of mycorrhiza, Moringa leaf fertilizer, and the consortium of both had a height of chili plants ranging from 21 cm at 28 day after planting (DAP) are higher than the control which was around 18 cm. The control treatment produced a lower number of leaves, namely 8.4 compared to the other three treatments with an average of 12 strands. The wet root weight of chili plants 30 DAP in the control was 2 grams, lower than the administration of mycorrhiza (4.2 grams), Moringa leaf fertilizer (4.2 grams), and the consortium of both (3.8 grams). The cross-section of the roots of chili plants in the three treatments was thicker than the control.